2020
DOI: 10.3389/fneur.2020.565088
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Pachymeningitis in a Southern Chinese Population: A Retrospective Study

Abstract: Aims: To investigate the causes, clinical characteristics, imaging features, and therapeutic implications of hypertrophic pachymeningitis (HP) in a southern Chinese population. Methods: We retrospectively analyzed 48 patients with HP with different causes from 1 January 2006 to 31 December 2018. Clinical manifestation, laboratory findings, and neuroimaging results were evaluated in all HP patients. Results: The mean age at onset was 50 ± 12 years. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 60 publications
1
8
0
1
Order By: Relevance
“…This study also demonstrated that headache and cranial neuropathies were common neurological symptoms associated with HP in both newly diagnosed and relapsed AAV, consistent with previous reports [ 8 , 10 , 15 20 ]. In addition, our results indicated meningitis and spinal cord lesion as significant conditions in patients with HP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study also demonstrated that headache and cranial neuropathies were common neurological symptoms associated with HP in both newly diagnosed and relapsed AAV, consistent with previous reports [ 8 , 10 , 15 20 ]. In addition, our results indicated meningitis and spinal cord lesion as significant conditions in patients with HP.…”
Section: Discussionsupporting
confidence: 93%
“…Several single-center studies on ANCA-associated HP have been presented to date; however, it might be difficult to accurately determine the clinical characteristics contributing to HP development in AAV because of the limited number of patients analyzed at each institution. Considering the ethnic viewpoint of ANCA-associated HP, the majority of published studies have been reported from East Asian counties including Japan [ 8 , 10 , 15 20 ]. Consequently, this was the first study to assess the clinical characteristics of HP using the enrolled information from many Japanese patients with AAV, demonstrating the epidemiological findings, especially the frequency of HP and classification in AAV, as more reliable results than those in single-institutional studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Headache is the most reported symptom and, in some cases, may remain the only presenting symptom for years [ 19 ]. In a retrospective cohort of patients, it was reported in 82%-98% of people with IHCP [ 20 ] and is thought to be likely attributable to dura mater inflammation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ne pai sant to, pa ste bë ta, kad idio pa tinio HP MRT vaiz dui la biau bû din gas hi poin ten si nis kie tojo dan ga lo T2 se kos sig na las su ho mo ge nið ku kon tras ti nës me dþia gos kau pi mu kie to jo dan ga lo krað tuo se [3]. Taip pat bû din ga kon vek si ta li në pa þei di mo lo ka li za ci ja ir su storë ji mas ties uþ pa ka li ne kau ko lës duo be, sme ge në liø padang te, tuo tar pu ant ri niam HP la biau bû din gas prie ki nës ir vi du ri nës kau ko lës duo bës pa þei di mas [3,5]. Ne sant speci fi niø kli ni ki niø ir ra dio lo gi niø idio pa ti nio HP po þy miø, svar biau sià vie tà ðios li gos diag nos ti ko je uþ ima ant ri niø HP prie þas èiø at me ti mas ir kie to jo dan ga lo biop si ja [4].…”
Section: Literatûros Apþvalgaunclassified